Kako doseči kakovost poslovanja v podjetju - pregledni članek - Bekrić, Merima (Revija za univerzalno odličnost, 2013)
Purpose: Determine which top management approaches are essential for business excellence and leadership approaches that achieve quality business. Method: Analysis of articles from the Journal Organization from the last 5 years and one article from the Journal of Universal Excellent to obtain data. Results: Characteristics of managers and individual employees influence the quality of an organization's performance and business excellence. This is rudimentary for an organization to perform successfully. The results show the weaknesses that an organization can improve in. Organization: The research study facilitates in improving long-term success of an organization. The results can assist in further decision-making and timely responses to changes in its internal and external environment. Society: Better business performance contributes to the wider environment, as this also ensures stability of an organization. Originality: A different approach in viewing management issues and searching for improvements. There are not many review articles on this topic. Limitations: The analysis was conducted with only ten articles.
Keywords: inovativnost; kvaliteta; management; organizacija; organization; podjetja; poslovna uspešnost; vodenje